Net Zero Healthy Building: Defining the Terms and Criteria with Bibliometric Analysis - Susan, Susan; Wardhani, Dyah Kusuma; Ariyanto, Yusuf; Wonohadidjojo, Daniel Martomanggolo; Harianto, Eric (EMARA: Indonesian Journal of Architecture, 2023)
Net Zero Energy Buildings (NZeBs) are a key design and construction paradigm due to sustainable building practices. NZeBs emphasize occupant well-being and reducing dependence on non-renewable energy sources in building design. A rigorous bibliometric investigation will define and standardize NZeBs in this work. This study uses data mining, VOSviewer bibliometric analysis, and a comprehensive literature search to identify key themes and criteria for understanding Net Zero Energy Buildings. The findings show that building system boundaries, passive design, energy efficiency assessments, and adaptive thermal comfort principles help conceptualize Net Zero Energy Buildings. This research improves our understanding of NZeBs and lays the groundwork for future research on sustainable building practices and healthier interior environments by merging data from other sectors.